Prediction of Insulin Resistance and Impaired Fasting Glucose Based on Sex Hormone-Binding Globulin (SHBG) Levels in Polycystic Ovary Syndrome - Aleksandra Biernacka-Bartnik; Piotr Kocełak; Aleksander Jerzy Owczarek; Piotr Choręza; Monika Puzianowska-Kuźnicka; Leszek Markuszewski; Paweł Madej; Jerzy Chudek; Magdalena Olszanecka-Glinianowicz (International Journal of Endocrinology)
Objective. Decreased synthesis of sex hormone-binding globulin (SHBG) related to hyperinsulinemia is one of the disturbances characteristic of polycystic ovary syndrome (PCOS). Hyperinsulinemia is a compensatory mechanism for liver insulin resistance (IR); thus, SHBG may be considered as a surrogate marker of liver IR. Therefore, this study aimed to assess the prediction of IR and impaired fasting glucose (IFG) based on SHBG levels in women with PCOS. Methods. This analysis included data retrieved from medical records of 854 patients with PCOS hospitalized in the Gynecological Endocrinology Clinic from 2012 to 2019. Data including anthropometric parameters, fasting plasma glucose, insulin, and SHBG levels were analyzed. BMI and HOMA-IR were calculated with standard formulas. Results. IFG and IR assessed based on HOMA-IR values > 2.0 were found in 19.5% and 47.8% of the study group, respectively. Empirical optimal cutoff values for SHBG levels were ≤41.5 nmol/L typical for IR (AUC 0.711, sensitivity 61.1%, specificity 71.6%, positive predictive value (PPV) 70.7%, and negative predictive value (NPV) 62.1%). The probability of insulin resistance occurrence for SHBG concentration 26.1 nmol/L (the lower normal range) was 61.6% (95% CI: 57.4%–65.8%). The SHBG concentration of 36.4 nmol/L and 8.1 nmol/L was related to a 10% and 20% probability of IFG, respectively. Conclusion. In conclusion, this is the first study estimating the probability of liver IR and IFG occurrence based on SHBG levels in women with PCOS. Despite the low sensitivity, SHBG level below 42 nmol/L should cause closer monitoring for the fatty liver and prediabetes.